Enhancing Employability: A Systematic Literature Review on the Significance of English for Occupational Purposes in Higher Education - Astarilla Dede Warman, Liya; Hadriana, Hadriana; Sumarno, Sumarno (AL-ISHLAH: Jurnal Pendidikan, 2024)
Employability of the graduates is the main issue that should be addressed by higher education institutions. The study aimed to investigate the implementation and importance of English for Occupational Purposes (hereinafter, EOP) to improve graduates’ employability. This study utilized a systematic literature review to synthesize the literatures related to EOP. There were 23 articles obtained from publication database and search engines namely ScienceDirect, Google Scholar and Semantic Scholar that were published between 2013 and 2023. This study found that the implementation of EOP has been conducted in several areas of disciplines in higher education namely aviation, engineering, healthcare, tourism, and hospitality around the world. Furthermore, EOP is important to improve students’ English communication skills in spoken and written form which contributes in improving students’ employability. Besides, EOP also enhances students’ soft skills in line with industry demand in the 21st century.